Fluorescence Polarization Control for On–Off Switching of Single Molecules at Cryogenic Temperatures. Issue 9 (30th April 2018) - Hulleman, Christiaan N.; Huisman, Maximiliaan; Moerland, Robert J.; Grünwald, David; Stallinga, Sjoerd; Rieger, Bernd
Abstract: Light microscopy, allowing sub‐diffraction‐limited resolution, has been among the fastest developing techniques at the interface of biology, chemistry, and physics. Intriguingly no theoretical limit exists on how far the underlying measurement uncertainty can be lowered. In particular data fusion of large amounts of images can reduce the measurement error to match the resolution of structural methods like cryo‐electron microscopy. Fluorescence, although reliant on a reporter molecule and therefore not the first choice to obtain ultraresolution structures, brings highly specific labeling of molecules in a large assembly to the table and inherently allows the detection of multiple colors, which enables the interrogation of multiple molecular species at the same time in the same sample. Here, the problems to be solved in the coming years, with the aim of higher resolution, are discussed, and what polarization depletion of fluorescence at cryogenic temperatures can contribute for fluorescence imaging of biological samples, like whole cells, is described. Abstract : Cryogenic super‐resolution fluorescence microscopy can be realized by utilizing fluorescence polarization control. Linearly polarized excitation and depletion lasers can be used to narrow the set of molecular dipole orientations that fluoresce. The enhanced cooling capacity and stability of the cryostat should enable resolutions down to the scale of individual emitters.